2015
DOI: 10.1016/j.jare.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pH elevation as a bactericidal strategy for treating ballast water of freight carriers

Abstract: Treatment of ship ballast water with sodium hydroxide (NaOH) is one method currently being developed to minimize the risk to introduce aquatic invasive species. The bactericidal capability of sodium hydroxide was determined for 148 bacterial strains from ballast water collected in 2009 and 2010 from the M/V Indiana Harbor, a bulk-freight carrier plying the Laurentian Great Lakes, USA. Primary culture of bacteria was done using brain heart infusion agar and a developmental medium. Strains were characterized bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Because of the simplicity of elevating water-system pH with NaOH, its potential use in confined pipes and in channels and tanks infested with nuisance mollusks may hold promise. Tests of ballast disinfection using additions of NaOH (Elskus et al 2015;Moffitt 2015a;Starliper et al 2015) suggested that not only was this chemical effective, but that after neutralization with CO 2 , the effluents would meet regulatory guidelines for safe discharge. Sodium hydroxide was registered as a herbicide many decades ago for control of tree roots in sewer systems, as a fungicide and algicide for use on water-well casings, and as a disinfectant in various indoor settings (USEPA 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the simplicity of elevating water-system pH with NaOH, its potential use in confined pipes and in channels and tanks infested with nuisance mollusks may hold promise. Tests of ballast disinfection using additions of NaOH (Elskus et al 2015;Moffitt 2015a;Starliper et al 2015) suggested that not only was this chemical effective, but that after neutralization with CO 2 , the effluents would meet regulatory guidelines for safe discharge. Sodium hydroxide was registered as a herbicide many decades ago for control of tree roots in sewer systems, as a fungicide and algicide for use on water-well casings, and as a disinfectant in various indoor settings (USEPA 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Elevating the pH of water with NaOH in freshwater ballast systems has been reported as highly effective to kill a suite of plankton and bacterial or viral species (Moffitt et al 2015a;Starliper et al 2015). The alkaline solutions in ballast tanks used can be neutralized with CO 2 , yielding environmentally harmless compounds that have been shown to meet effluent guidelines (Elskus et al 2015;Moffitt et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…This NaOH content can inhibit the growth and production of bacterial enzymes. For example, NaOH or sodium hydroxide in pH 12 for 24 hours could kill bacteria [24]. NaOH in low concentrations can be bactericidal.…”
Section: (A) (B) (C) (D) (E)mentioning
confidence: 99%
“…The use of ballast tanks to transport a slurry of SL could avoid the necessity of a dedicated cargo hold, and at the same time has the benefit of avoiding the treatment of ballast water (or at least reducing treatment costs), currently mandatory because ships are a major vector for the introduction of nonindigenous and harmful organisms (Johnson and McMahon, 1998;Sousa et al, 2008). pH increase through the addition of alkaline materials (one of which is calcium hydroxide) is an efficient and cheap ballast water treatment strategy (Starliper et al, 2015), since it kills the aquatic nuisance species that cause economic and ecological damages to oceans. International legislative constraints should be evaluated to understand the possibility of discharging SL slurry; ballast water treatment with SL is still not among the authorized treatment methods (IMO-International Maritime Organization, 2008).…”
Section: Use Of Ballast Water Tanks Of Existing Shipsmentioning
confidence: 99%